Problems of early culling of cows in breeding stocks for milk production - Perišić Predrag; Relić Renata; Mekić Cvijan; Stepić Stefan (Biotechnology in Animal Husbandry, 2020)
A common problem of dairy cattle in all production systems and production directions is their reduced production life and therefore their reduced lifetime span. Among the main reasons of dairy cattle premature culling the problems related to reproduction, udder and legs are prevailing. The order of these reasons according to their significance is not the same in all dairy cattle populations and depends on production direction, level of production and specific technology of cattle breeding. There are also other reasons of culling but these three groups are the main ones. Due to frequency of their incidence, as well as economic damage which they can cause in dairy cattle production, today they must be taken into account when defining breeding goals for certain breeds and populations of cattle.